High blood carbon dioxide variability and adverse outcomes in neonatal hypoxic ischemic encephalopathy. (16th February 2016) - Hansen, Gregory; Al Shafouri, Nasser; Narvey, Michael; Vallance, Jeff K.; Srinivasan, Ganesh
Abstract: Objective : Hypocarbia during the first 12 h of life is associated with mortality and disability in neonatal hypoxic ischemic encephalopathy (HIE). Notable variation in arterial carbon dioxide tension (PaCO2 ) during the first 4 d of life is related to severe intraventricular hemorrhages in preterm infants. We examined the association between PaCO2 during 72 h of whole-body therapeutic hypothermia for neonatal HIE and 2-year neurodevelopmental outcomes. Methods : A retrospective review of 23 term neonates treated with whole-body hypothermia documented clinical, demographic and arterial blood gas data. Comparisons were made across good and severe neurodevelopmental outcome groups at 2 years of age. Results : Severe neurodevelopmental outcomes were documented in 8 of 23 toddlers. There were no significant differences between outcome groups with regard to the number of patients with hypocarbic means or measurements. There were also no significant differences with mean PaCO2, PaO2, pH, time-weighted cumulative hypocarbia, and PaCO2 range. The severe neurodevelopmental outcomes group had a significantly higher mean PaCO2 standard deviation ( p = 0.04; 95% CI, −5.46 to −0.39). Conclusion : Severe neurodevelopmental outcomes were significantly associated with high PaCO2 variability over 72 h in whole-body-cooled HIE neonates. Mitigating these fluctuations may be a potential management strategy.